Intervening sequence with conserved open reading frame in eubacterial 23S rRNA genes. - Ralph, D (1993)
An intervening sequence (IVS) occurred in the 23S rRNA genes (rrl) of some, but not all, strains of four species of the spirochete genus Leptospira and was absent from strains in three other species. The IVS varied in size from 485 to 759 base pairs and replaced bases 1224-1245 in both copies of rrl. The two ends of each IVS shared 22-35 bases of complementarity that could form a stable double helix. The presence of an IVS correlated with a cleaved mature 23S rRNA that probably results from removal of the IVS without religation. The 3' site of cleavage was mapped within the inverted repeat of the IVS. An open reading frame of 121-133 amino acids was conserved in the IVS in all four species, oriented so that the sense strand was in the rRNA transcript. When the open reading frames were compared between species, they predicted polypeptides that showed between 51% and 78% amino acid conservation and similar DNA sequence conservation, indicating selection for protein function.